Implementasi Nilai Persatuan dalam Pendidikan Karakter Serta Rasa Percaya Diri Sebagai Mahasiswa Perguruan Tinggi - Rayhan Zain Alfataa; Edy Soesanto; Marchell S P Siburian (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
In the journey of life, especially in the world of higher education, students are faced with various challenges that not only test their intellectual abilities, but also their personalities. Among the values that are essential to forming individual character, unity is an element that is often overlooked, but has a profound impact on the formation of character and self-confidence for college students. Unity is not just a figment of the imagination, but an important foundation in living life with full strength and emotional balance. National unity is a solid foundation for the younger generation to achieve a bright future. In the era of globalization that is full of dynamics, unity becomes increasingly crucial. Without unity, various challenges such as division, radicalism, and instability will threaten the sustainability of the nation. The younger generation as agents of change has a central role in maintaining and strengthening unity. By uniting, the younger generation can create strong synergy to overcome various problems and advance the nation.